The reality of curricula in information and library departments in Iraqi institutes A comparative study with models in Arab and foreign institutes (Journal of the College of Basic Education, 2022)
The study aimed at analyzing programs and study plans offered by information departments and libraries in Iraqi institutes and identifying their current reality by comparing them with their counterparts in Arab countries and advanced global models from Canada, the United States of America and Australia, identifying the shortcomings and strengths in these plans and curricula. The study included information and library departments in the three Iraqi institutes (administrative / Rusafa, technical / Mosul, administrative technical / Erbil), and information and library departments in the Arab countries (Jordan, United Arab Emirates, Palestine), and models of international library and information departments in each of ( Canada, the United States of America, Australia), and the study used two research methods: